Direct Radiative Effect of Absorbing Aerosols: Sensitivity to Mixing State, Brown Carbon, and Soil Dust Refractive Index and Shape. Issue 2 (22nd January 2020) - Tuccella, Paolo; Curci, Gabriele; Pitari, Giovanni; Lee, Seungun; Jo, Duseong S.
Key Points: Aerosol absorption is sensitive to mixing state, brown carbon, and soil dust optical properties Blanching reduces coating brown carbon radiative effect; soil dust radiative effect uncertainty due to the refractive index is large Radiative effect of radiation‐absorbing aerosol total uncertainty is mainly due to dust refractive index and brown carbon treatment Abstract: Black carbon (BC), brown carbon (BrC), and soil dust are the most relevant radiation‐absorbing aerosols in the climate system, and uncertainties of their absorbing optical properties are large. We performed a 5‐year simulation with the GEOS‐Chem global chemistry and transport model and calculated the aerosol optical properties testing different mixing state assumptions and absorption properties of BC and BrC, refractive index, and shape of soil dust. We found that the core‐shell (CS) internal mixing representation produces the most accurate absorption aerosol optical depth and single‐scattering albedo at Aerosol Robotic Network (AERONET) Sun photometers site observations dominated by carbonaceous absorption. Dust absorption is sensitive to the assumed refractive index. The nonspherical shape of dust improves the simulation at sites dominated by dust absorption. Global mean of all‐sky direct radiative effect (DRE) by BC is +0.13 and +0.25 W/m 2 for external and CS mixing state assumptions, respectively. Adding BrC in CS mixing state, the BC‐BrC DRE mixture increases to +0.40 W/m 2, indicating an absorption enhancement with respect to external mixing state of +0.27 W/m 2, which is less than the +0.51 W/m 2 previously reported. The difference is attributed to the inclusion of the blanching process of BrC from biomass burning. Dust DREs are −0.10, +0.11, and +0.22 W/m 2 for "low, " "middle, " and "high" dust absorption scenarios, respectively. Considering the nonspherical shape, these values change by up to 0.03 W/m 2 . All‐sky DRE by all radiation‐absorbing aerosols is +0.46 W/m 2 . Aerosol mixing state, BrC treatment, and dust optical property uncertainties suggest a total DRE uncertainty of −57%/+59%.